(3QSGdI aj PcQ GdQO Ydi Cgd GdJChjds - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdPjf jhLHhf JcQGQ GdEdg ai GdCbeUI GdeNJdaI jbGd dge gd GdEdg YGOd Ce LGFQ XGde s
(3BNQgG (B:s
(3aef YQag fGd GdNjQGJ hGfVdJ Hg GdahGFO GdYbdjGJ hRGd Yf bdHg GdYdhe GdhgejGJ GdeaSOI ddUhQ hgh MSHi hKbJi HGdbGFe hcai s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B74s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds